Menumbuhkan Jiwa Kewirausahaan Melalui Kreativitas Buket Snack Pada Karangtaruna RW 5 Kelurahan Salamanmloyo Semarang - Chasanah, Amalia Nur; Puspitasari, Diana; Wardhani, Masitha Fahmi; Ulfa, Adilla Kustya (Lembaga Dongan Dosen, 2025)
Entrepreneurship is an option for the younger generation in creating a better economy. However, knowledge about entrepreneurship is still limited, especially among the younger generation, especially in the Karang Taruna RW 5, Salaman Mloyo, Semarang. Activities currently carried out by Karangtaruna include social activities such as sorting rubbish, holding certain activities such as commemorating August 17 and other activities. In order to develop an entrepreneurial spirit in members, various activities and training are needed to increase members' skills. Based on this, the service activity carried out is to foster an entrepreneurial spirit through the creativity of snack bouquets for teenagers from Karangtaruna RW 5, Salaman Mloyo, Semarang. The aim of this activity is to improve the entrepreneurial spirit and develop innovation in youth organizations. The expected results of this activity are the growth of the entrepreneurial spirit, increased insight into entrepreneurship and the growth of innovation for members of Karang Taruna RW 5, Salaman Mloyo, Semarang.